Ecoliteracy Study About Lake Toba On High School Students - Pardede, Lastiar H; Manurung, Binari; Silitonga, Melva (Journal of Learning Improvement and Lesson Study, 2024)
Responding to the increasingly critical condition of the Lake Toba ecosystem over time, including in the Toba Regency area, research related to ecoliteracy needs to be carried out. The purpose of this study is to measure the level of ecoliteracy abilities of high school students in Toba Regency based on 3 aspects (cognitive, affective, and behavior) and how the relationship between the three aspects of ecoliteracy abilities. The method used in this research is a survey method with a descriptive quantitative approach. Data collection techniques were carried out using tests, distributing questionnaires, and FGD activities. The results showed that the ecoliteracy abilities of students were in the "medium" category, with x̄ = 106.76 which gave different values to each aspect measured. Cognitive and behavioral aspects are in the "medium" category, while affective aspects are in the "high" category. Through this study, the Pearson correlation test results were also obtained (p>0.05) which showed that there was a significant relationship between cognitive, affective, and behavioral aspects with overall ecoliteracy abilities.